PENGGUNAAN METODE DEKOMPOSISI-ARIMA DALAM MERAMALKAN TINGKAT PENGEMBALIAN SAHAM PADA EMITEN TERPILIH DI BURSA EFEK INDONESIA PERIODE 2003-2007 - Septia, Tika (Universitas Ahmad Dahlan, 2012)
The public has many ways to invest money, one of them by buying obligation in the capital market. A rational investor should consider the expected income and risk of alternative investments contained does. The study was conducted to determine the rate of return/ total risk of stocks returns and investment in the company/ issuer elected and predict stock returns one year later. Analysis of the data used are time series analysis using decomposition-ARIMA method. The data used in this study is the stock return of monthly data from January 2003 to December 2007. Analysis of stock returns from January 2003 to December 2007 showeda trend of rising prices down. Fluctuations in stock returns peaked in August 2004. Decomposition method is used to forecast the trend and seasonal component, while the ARIMA method is used to predict cyclical and random components. Decomposition method used is the multiplicative decomposition. The best ARIMA models used to predict cyclical and random components of the ARMA (2,1) in equation form as follows :0,6286 + 0,3480 + - 0,9361 The value of MAPE = 17,89 % dan MSE = 9,471. Forecastong is done to show that the lowest return in January is the right position to buy the stock, while the highest return in March is the right position to sell the stock.